2017
DOI: 10.1007/s40675-017-0062-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factors and Cancer

Abstract: Purpose Of Review Hypoxia inducible factors (HIFs) mediate the transcription of hundreds of genes that allow cells to adapt to hypoxic environments. In this review, we summarize the current state of knowledge about mechanisms of HIF activation in cancer, as well as downstream cancer-promoting consequences such as altered substrate metabolism, angiogenesis, and cell differentiation. In addition, we examine the proposed relationship between respiratory-related hypoxia, HIFs, and cancer. Recent Findings HIFs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(140 citation statements)
references
References 133 publications
(125 reference statements)
2
119
0
1
Order By: Relevance
“…Our studies demonstrated that the 3D-O model while supporting BCa cell growth, simulated physiological oxygen levels and generated intratumoral hypoxic hallmarks such as increased HIF expression (Figure 3). Upregulated HIF expression is a well-known parameter associated with hypoxia and is known to affect several downstream biochemical processes (89). Our results confirm that oxygen deprivation within 3D-O can efficiently reiterate HIF-driven regulation in the resident BCa cells.…”
Section: Immune Cell Infiltration Into 3d Matrices Has Been Observedsupporting
confidence: 79%
“…Our studies demonstrated that the 3D-O model while supporting BCa cell growth, simulated physiological oxygen levels and generated intratumoral hypoxic hallmarks such as increased HIF expression (Figure 3). Upregulated HIF expression is a well-known parameter associated with hypoxia and is known to affect several downstream biochemical processes (89). Our results confirm that oxygen deprivation within 3D-O can efficiently reiterate HIF-driven regulation in the resident BCa cells.…”
Section: Immune Cell Infiltration Into 3d Matrices Has Been Observedsupporting
confidence: 79%
“…Targeting the HIF pathway in cancer is quite challenging due to the heterogeneity of the target genes and also their different regulation dependent on the cancer types [135]. Currently, there are several therapeutics in preclinical testing able to block HIF activity with the intention of limiting the tumor development, angiogenesis, and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…However, none of these small molecules were designed for specific targeting of HIF-1α, fact that hampers the translational switch toward the patients due to difficulties in controlling the level of action and selection of the targeted cohort [137]. There are also clinical approved drugs that were shown to interfere with HIF-1α activity (non-specific HIF-1α inhibitors): Angiotensin-2 receptor blocker, digoxin or metformin [135,138,139]. Prostate cancer patients prescribed with one of these three therapies have been associated with decreased risk of cancer progression [140].…”
Section: Resultsmentioning
confidence: 99%
“…HIF1 is a key sensor of oxygen availability. In normoxia, HIF1 is hydroxylated and rapidly degraded, whereas under hypoxic conditions, HIF1 hydroxylation is reduced, leading to stabilization of HIF1 expression levels . The two subunits of HIF1, α and β, function as transcription factors, resulting in enhanced expression of specific genes that promote survival during hypoxia .…”
Section: Regulation Of Endocytic Traffic By Hypoxiamentioning
confidence: 99%